Towards Healthy Tribal Communities: A Comprehensive Commentary on Initiatives in India - Joshi, Abhishek; Raut, Juhi M; Mudey, Abhay (Indian Journal of Community Health, 2025)
Background:Tribal people also called as Indigenous people have diverse languages, cultures, traditional practices or rituals, and customs that distinguish them from the rest of the civic world. Although there are around 104 million tribal people in India they have remained socio-demographically and geographically distant and suffer from various health ailments from communicable diseases like Malaria Tuberculosis and malnutrition to increasing burden of Hypertension and Diabetes. The various health parameters and indicators remain below the National average. The detailed report of Expert committee on tribal health has led the way for various Government ministries and departments to work on addressing the disparity in Tribal health. Aim & Objectives: To summarize and collate all the existing measures for improving tribal health parameters Methodology: We included all the National and International policies and programs along with some examples from Non Government sectors and recent updates. Results: This article summarizes all the initiatives and efforts being undertaken in India by all the stakeholders along with updates on some recent initiatives to understand the holistic efforts towards achieving Holistic Tribal development and how medical colleges can complement these efforts. Conclusion: We collated the overall evidence for creating a comprehensive commentary on Tribal Health initiatives.